Design and Fabrication of Plastic Compressor Machine for Plastic Waste - Rosmanizan, Ida; Nor, Fethma M (INSTEP Network, 2021)
This project work is on design and fabrication of a plastic compressor machine to compress plastic waste. The objective of this project is to help to reduce plastic waste mostly from domestically usage and turn into a paving brick that can be uses as decoration in a mini garden or walkway. This plastic compressor machine works using a modified old conventional oven to melt shredded plastic waste in a mould and let the melted plastic cooled and turned to a paving brick. The temperature to melt the shredded plastic waste of 450 grams is 250 degrees Celsius in 1 hour. The machine fabricated using recycled materials, which makes it cheap, easy to maintain and affordable.